"A new phoenix, of the more worthier gender" : reinforcing the gender hierarchy and patriarchal orthodoxy on the Jacobean stage, 1603-1606 : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in English at Massey University, Albany, New Zealand - van Geffen, Elizabeth Eve (Massey University, 2021)
Focusing on the early years of James I’s reign in England – specifically, 1603 to 1606 – I explore how, after more than half a century of female rule in England, the restoration of male monarchy in England foregrounded misogynistic gender expectations, and how the early modern theatre had a hand in the reinforcement of the gender hierarchy and patriarchal orthodoxy. Analysing thirteen extant plays first performed professionally in London theatres within this date range, this project explores how early modern ideas of ‘masculinity’ and ‘femininity’ played out on the stage at a time when a female to male transition of monarchical power promoted a heightened awareness of, and anxieties regarding, gender and the gendered social order. I also examine how violations of the gender hierarchy and social order were framed, theatrically, as transgressive and dangerous, and how, in some instances, these social threats were ‘contained’ so as to consolidate patriarchal orthodoxy. Employing a broadly new historicist approach, my analysis of the plays is complemented by research drawing on a range of early modern English discourses which equally informed and were informed by the patriarchal hierarchies underpinning social thought at this time. These include the sumptuary laws and regulations, humoral theory and pseudo-medical treatises, anti-theatrical tracts, political treatises and speeches, topical pamphlets, poetry and panegyrics. These discourses showcase that the plays under examination in this research project are a product of a historic moment preoccupied with the maintenance and preservation of a social order that revolved around patriarchal power. Ultimately, this thesis will demonstrate that the plays themselves implicitly and explicitly maintained and preserved this patriarchal order. However, my research identifies a surprising nuance in the reinforcement of this power/order, demonstrating that the binary gender hierarchy was complicated by the early modern recognition of subtle gender differences within a sex.
Keywords: 470504 British and Irish literature